2022
DOI: 10.1021/acs.inorgchem.2c01525
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport and Photoconductivity in a Hybrid Uranium(IV) Halide Perovskite

Abstract: Hybrid metal halide perovskites are extensively synthesized using p-and d-elements. However, the properties of hybrid halide perovskites involving 5f-elements are still elusive. Herein, we first report the semiconductive property of a uraniumbearing hybrid halide perovskite, [N(C 2 H 5 ) 4 ] 2 UCl 6 (EAUCl). Single crystal X-ray crystallography demonstrates that EAUCl adopts a zero-dimensional molecular structure consisting of isolated [UCl 6 ] 2− anions and organic cations. The intrinsically semiconductive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The leakage current of the device was measured at a level of 10 −10 A when testing the sample in a dark field without X-rays under an applied bias voltage ranging from −30 to 30 V. The resistivity of the sample was calculated to be 2.797 × 10 9 Ω•cm, which confirms the examination requirement for conventional semiconductors for X-ray detection. 29 Compared with its dark counterpart, U-DPDPP exhibited a significant response to X-ray excitation, as demonstrated in Figure 3a, with the current increasing by 2 orders of magnitude. It is suggested that there is significant charge carrier generation and charge transport in U-DPDPP under Xray irradiation.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The leakage current of the device was measured at a level of 10 −10 A when testing the sample in a dark field without X-rays under an applied bias voltage ranging from −30 to 30 V. The resistivity of the sample was calculated to be 2.797 × 10 9 Ω•cm, which confirms the examination requirement for conventional semiconductors for X-ray detection. 29 Compared with its dark counterpart, U-DPDPP exhibited a significant response to X-ray excitation, as demonstrated in Figure 3a, with the current increasing by 2 orders of magnitude. It is suggested that there is significant charge carrier generation and charge transport in U-DPDPP under Xray irradiation.…”
mentioning
confidence: 95%
“…A single-crystal sample (1.2 mm × 1.1 mm × 0.9 mm) was affixed to a small circuit board using conductive silver adhesive and copper wire for X-ray irradiation. The leakage current of the device was measured at a level of 10 –10 A when testing the sample in a dark field without X-rays under an applied bias voltage ranging from −30 to 30 V. The resistivity of the sample was calculated to be 2.797 × 10 9 Ω·cm, which confirms the examination requirement for conventional semiconductors for X-ray detection …”
mentioning
confidence: 99%